2018
DOI: 10.3389/fphar.2018.00951
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial: Regenerative Effects, Efficacy and Safety of Erythropoietin in Burn and Scalding Injuries

Abstract: In adult’s burn injuries belong to the top 15 causes of injury. Annually more than a million patients receive specialized treatment. Improving burned patients’ outcomes is still a challenge. Effects of erythropoietin (EPO) are reported to be pro-angiogenic, pro-regenerative, anti-inflammatory, immunomodulatory and hypoxia/ischemia protective. Study objectives were to demonstrate cytoprotective and regenerative effects of EPO in burned patients in terms of improved wound healing, reduced morbidity and mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
0
10
0
2
Order By: Relevance
“…In the previously published main findings of the "EPO in Burns" study, EPO was found to be safe in severely burned patients. In addition, an organ protecting and stabilizing effect in severely burned patients (SOFA score) and an earlier onset of wound healing in the EPO group was demonstrated (Gunter et al, 2018).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In the previously published main findings of the "EPO in Burns" study, EPO was found to be safe in severely burned patients. In addition, an organ protecting and stabilizing effect in severely burned patients (SOFA score) and an earlier onset of wound healing in the EPO group was demonstrated (Gunter et al, 2018).…”
Section: Introductionmentioning
confidence: 86%
“…Thromboembolic events could thus be reduced to ranges seen in poly-traumatized patients not receiving EPO when combined with appropriate anti-thrombotic therapy (Corwin et al, 2007). In our previous publication of "EPO in Burns," we presented primary and secondary endpoint analysis data, including safety, regenerative effects, and efficacy of systemically applied (s.c.) EPO in split skin graft donor sites, as well as in burn and scald injuries, and severely burned patients (Gunter et al, 2018). However, the analysis of the primary endpoint of the "EPO in Burns" study regarding the complete reepithelialization of a defined split skin graft donor site (= the study wound) did not show conclusive results regarding EPO effects on wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that the administration of low doses of EPO improves wound healing in patients with diabetes without affecting the hematocrit level [26]. In RCTs, Guenter EPO was used to treat burns [27]. However, the results (epithelialization of burn wounds) were inconclusive.…”
Section: Premise For Using Epo For Wound Healingmentioning
confidence: 99%
“…В РКИ К. Guenter ЭПО применяли для лечения ожогов [35]. При этои результаты (эпителизация ожоговых ран) были неубедительными.…”
Section: обзорыunclassified